From Wildflowers to Crops: An Exploration of Plant Adaptations to Human Influence - Irshad Ahmad Wani; Zakir Hussain Mir (PT. Radja Intercontinental Publishing, 2025)
This research explores the transformation of wild plant species into domesticated crops through evolutionary adaptations influenced by human intervention. By examining the processes of artificial selection, genetic modification, and environmental changes driven by agriculture, the paper uncovers how plant traits such as seed dispersal, resistance to pests, and growth patterns have been shaped. The study integrates insights from evolutionary biology, agricultural science, and ecology to highlight the complex interaction between natural systems and anthropogenic pressures, shedding light on the future of sustainable crop development and biodiversity conservation.